The Factors Related To The Event Baby Blues In Postpartum Mothers: Postpartum Mothers - Dedi Krismiadi; Apriyanti Apriyanti; Hasniah Dina (STIKes Mandala Waluya Kendari, 2023)
Background: Baby blues is a mild affective disorder syndrome that often appears in the first week after delivery and tends to get worse on the third to fifth day and lasts for two weeks. The incidence rate increased in 2020 to around 70-80% of postpartum mothers experiencing baby blues syndrome and around 10-13% continued with postpartum depression. Postpartum blues hurt pregnant women and their unborn fetuses. This study aimed to determine the relationship between factors that influence the incidence of baby blues in postpartum mothers in the working area of the Bungku Tengah health center, Bungku Tengah sub-district, Morowali district. Methods: The research used the quantitative method through a cross-sectional study approach. The population in this study was 24 people with a total sampling technique with a total sample of 24 postpartum mothers. The instrument used was the Edinburgh Postpartum Depression Scale (EPDS). The analytical method uses the Chi-Square statistical test and the Phi coefficient (ⱷ). Results: Based on the study's results, there is a strong relationship between the incidence of baby blues and age, husband's support, parity level, and maternal employment. The p values (ⱷ) respectively (0.001, 0.001, 0.001 and 0.003) <0.05, which means that Ho is rejected and Ha is accepted, thus there is a relationship between age, husband's support, parity level, maternal employment with the incidence of baby blues among postpartum mothers in the working area of the Bungku Tengah Community Health Center, Bungku Tengah District, Morowali Regency). Conclusion: There is a relationship between age, husband's support, parity level, and maternal employment with the incidence of baby blues among postpartum mothers in the working area of the Bungku Tengah Community Health Center, Bungku Tengah District, Morowali Regency.